Identifying future growth potentials: a consolidated approach - Tilman Altenburg; Wilfried Lütkenhorst (Deutsches Institut für Entwicklungspolitik (DIE), 2017)
When Alice in Wonderland wonders which way she should take, the Cheshire Cat responds that it depends on where she wants to go! Researchers and policy-makers considering a country's long-term development path also have to know where they want to go. Typically, they seek to determine the realistic growth potentials for a country's economy and how to reach them, and identify the key assets that could make the country competitive and the economic sectors that should be prioritised to drive structural change. Most critically, they have to find out how to reconcile narrow goals regarding competitiveness and productivity with broader goals related to social inclusiveness and environmental sustainability. The challenge is to design a methodology for evidence-based anticipation of future competitive advantages that merit industrial policy measures. The sectors that could create viable growth must be understood. Identifying a country's competitive advantage in five to 10 years presents a thorny methodological challenge and a complex set of factors to consider, including: available domestic resources, institutional capabilities, production costs relative to other countries, geographic conditions, the country's position within the global trade and investment system (including expected changes in relevant regulatory regimes), and also long-term shifts towards new technological domains. More often than not, the analytical, conceptual and institutional preconditions for such an exercise exceed the capabilities of developing countries and constitute a core area of advisory services provided by development cooperation partners. Against this backdrop, we explore three aspects of possible methodologies: 1. The strengths and weaknesses of various contemporary methodologies, all of which fail to include important determinants of future competitive advantages. Since they do shed light on various complementary aspects, however, we suggest combining them to create a more complete picture of emerging opportunities. 2. The growing role of disruptive structural change. We are already confronted with radical and rapid structural change that impacts virtually all economic sectors and disrupts the prevailing techno-economic trajectory (seemingly the case for both decarbonisation and digitalisation). What are the methodlogical implications for predicting future competitive advantages? We recommend a stronger emphasis on using `open' qualitative forecasting methods. 3. Evidence-based approaches for measuring competetiveness and anticipating its future direction must be embedded into a political economy framework that connects analytical tools to societal objectives and accounts for the different implementation capabilities of various countries. Essentially, we argue that there is no `silver bullet' methodology for predicting emerging patterns of competitiveness. However, a variety of tools can be used to reduce the number of promising options and inform policy-makers about how to exploit emerging opportunities.
Keywords: 330; Armut und Ungleichheit; Technologie und Innovation